An Analysis of Students’ Critical Thinking Ability in Solving Jumping Task Questions based on Learning Style - Trapsilasiwi, Dinawati; Jatmiko, Dhanar Dwi Hary; Pambudi, Didik Sugeng; Ambarwati, Reza; Alim, Fathul ((JIML) JOURNAL OF INNOVATIVE MATHEMATICS LEARNING, 2023)
Critical thinking ability is the ability that must be possessed by all students in order to solve the problems encountered. Research that can reveal the critical thinking skills of students needs to be done. This study aims to describe the critical thinking skills of junior high school students in Jember in completing the jumping task problem in terms of learning styles in the material system of two variable linear equations. This type of research is qualitative descriptive research. The data collection method used is a questionnaire for learning style, critical thinking ability test questions based on jumping tasks, and interviews. The subject consists of three subjects from the single learning force category. Based on data analysis, students with a visual style can complete three jumping task questions and are able to fulfill five critical thinking ability indicators, namely focus, reason, inference, situation, and clarity. Students with an auditorial style can complete three jumping task questions and are able to fulfill five indicators of critical thinking skills: focus, reason, inference, situation, and clarity. Students with a kinesthetic style can solve only one question and fulfill five indicators: focus, reason, inference, situation, and overview. Suggestions Further research can see the critical thinking skills of students with double learning styles.